DETERMINANTS OF CLEAN AND HEALTHY LIVING BEHAVIOR AMONG PUBLIC ELEMENTARY SCHOOL STUDENTS IN BULANJULU - Tarigan, Fitri Fatmala Br; Hartono, Hartono; Pane, Putri Yunita (LPPM Univ. Ibn Khaldun Bogor, 2025)
Practicing Clean and Healthy Living Behavior (CHLB) plays a vital role in developing students’ healthy habits from a young age. At Bulanjulu Village Elementary School, the application of CHLB is affected by factors such as students’ knowledge, the role of teachers, and the availability of sanitation facilities. This research employed a quantitative descriptive method with a cross-sectional design, involving all 32 students from grades III to VI. Data were gathered through questionnaires and observations, then analyzed using the chi-square test. The findings revealed a significant correlation between knowledge level (p = 0.000) and teacher roles (p = 0.001) with the practice of CHLB, while observations revealed generally adequate sanitation facilities, though improvements were needed in canteen hygiene, waste management, and handwashing facilities. These findings indicate that enhancing students’ knowledge, strengthening teacher involvement, and improving facilities can effectively promote CHLB. In conclusion, sustainable educational interventions and facility improvements are necessary to create a healthy and supportive school environment.